Peran Guru dalam Mengembangkan Moral Agama Anak Usia Dini di Taman Kanak-kanak Aisyiyah Bustanul Athfal III Pekanbaru - Rahmah Rahmah; Armizi Armizi (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2022)
In developing morals and religion, early childhood requires the role of the teacher to nurture, educate, train, guide and always provide reinforcement and motivation, so as to make children interested and accustomed to doing so, in the sense that children have been accustomed to having morals and religion. Data collection was carried out by conducting observations, interviews, and documentation, and for this study using descriptive qualitative research methods, namely explaining and explaining data from research results. The method used in this research is descriptive method, by collecting data, compiling data, or classifying, analyzing and interpreting it. The results showed that the teacher's role in developing children's morals and religion in TK Aisyiyah Bustanul Athfal III Pekanbaru.